Viscosity and Thermodynamic Properties of Alkali Metal Bromides in the Presence of Acetonitrile, 3-Hydroxypropionitrile and Acetonitrile + 3-Hydroxypropionitrile Mixture at Various Temperatures - Shama,; Fahim Uddin,; Tehseen Ahmed ,; Talat Zamir, (Journal of Basic & Applied Sciences, 2013)
Excess molar volume VE/m, energy of activationΔEv, Gibbs energy change Gand entropy change Shave been investigated for this study density and viscosity measurements of Acetonitrile (AN), 3-hydroxypropionitrile (3-HPN) and 50% mixture of AN + 3-HPN and alkali metal bromides (Li,Na,K,Rb and Cs)Br in AN, 3-HPN and 50%AN+3-HPN over the concentration range (0.01 - 0.05 mol.dm-3) at temperature range (298 to 323 K) were used. On the basis of Jones-Dole Equation the viscosity B-coefficient and the thermodynamic, activation parameters for viscous flow of solutions have been evaluated. The B-coefficient values of LiBr, NaBr , KBr, RbBr and CsBr are positive and decreases by increasing the temperature. The B-coefficient values are positive in protic and aprotic solvents. The positive values reveal that electrolytes behave as structure maker